Cloudnymous Network and Data Security Model for Cloud (International Journal of Scientific Research and Management (IJSRM), 2017)
The world is having a tremendous need and hence is moving towards anywhere data and any-time computing. After intensive researches in the distributed computing arena, combined with the advancement in the internet, cloud computing has emerged as a highly successful concept. But this success is limited to, and to an extent, even threatened by security concerns which not only adds to the vulnerability of the cloud network but also questions the data integrity for the tenants who adopt cloud technology. To address this information security concern, this paper proposes cloudnymous network with IP validation during login and secured data model using Advanced Encryption Standard (AES) algorithm. Information theoretic anomaly detection implemented in this model helps in identification, detection and filtrations of anomalous data in a dataset, using pre-defined conditions and rules that will define the boundaries of correct data. This enhanced architecture improves the effectiveness of cloud usage by gaining the trust of the tenants due to secured network and data.